Splenic B-1a Cells Expressing CD138 Spontaneously Secrete Large Amounts of Immunoglobulin in Naïve Mice - Nichol E Holodick; Teresa eVizconde; Thomas L Rothstein (Frontiers in Immunology, 2014)
B-1a cells constitutively secrete natural antibody that provides immediate protection against microbial pathogens and functions homeostatically to speed removal of apoptotic cell debris. Although B-1a cells are especially prominent in the peritoneal and pleural cavities, some B-1a cells reside in the spleen. A small subset of splenic B-1a cells in naïve, unimmunized mice express CD138, a recognized plasma cell antigen, whereas the bulk of splenic B-1a cells are CD138 negative. Splenic B-1a cells in toto have been shown to generate much more antibody per cell than peritoneal B-1a cells; however, specific functional information regarding CD138+ splenic B-1a cells has been lacking. Here we find a higher proportion of CD138+ splenic B-1a cells spontaneously secrete more IgM as compared to CD138- B-1a cells. Moreover, IgM secreted by CD138+ splenic B-1a cells is skewed with respect to N-region addition, and some aspects of VH and JH utilization, as compared to CD138- splenic B-1a cells and peritoneal B-1a cells. The small population of CD138+ splenic B-1a cells is likely responsible for a substantial portion of natural IgM and differs from IgM produced by other B-1a cell subsets.